Analysis of The Internal Control System for Providing Credit in KPRI Handayani Takalar District - Nurrahmadani, Aulia Suci; Idrus, Mukhammad; S, Masnawaty (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
This research aims to find out and analyze whether the internal control system in providing credit at the Handayani Republic of Indonesia Employees Cooperative (KPRI) Takalar Regency is in accordance with the components in the COSO theory. The variable in this research is the internal control system for providing credit. The population in this research are all documents related to the internal control system at KPRI Handayani and the samples in this research are documents related to the internal control system for the 2022 financial year. Data collection techniques in this research are by observation, interviews, and documentation. This research uses qualitative data analysis techniques with a descriptive approach. The results of this research indicate that internal control in granting credit to KPRI Handayani is not fully implemented in the internal control components according to COSO as stated by Sujarweny (2015). Inappropriate components include: control environment, risk assessment, and control activities, information and communication, and monitoring. In the internal control environment, integrity and ethical values are not made in writing and are only given verbally. Apart from that, there is a commitment to competence which only acts based on trust. In the risk assessment there are no documents used to analyze risk and Standard Operating Procedures (SOP) regarding credit provision have not been created. Then in control activities there are no documents related to the authority for each transaction. Regarding information and communication where you don't use the application to view transaction history but it is still manual. As well as monitoring that is not carried out by regular audits.